2008
DOI: 10.5465/amj.2008.34789675
|View full text |Cite
|
Sign up to set email alerts
|

Former Government Officials as Outside Directors: The Role of Human and Social Capital

Abstract: The resources that individual directors bring to corporate boards are largely a function of their human and social capital. Although research has explored the value of having former federal government officials join boards, we study factors that make one particular former government official more, or less, attractive as a director than another. Specifically, we explore the depth, breadth, and deterioration of former government officials' human and social capital and find that these dimensions of human and soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
300
0
11

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 342 publications
(317 citation statements)
references
References 68 publications
6
300
0
11
Order By: Relevance
“…It might simply be that firms benefit from moonlighting politicians via the introduction of important additional human and social capital (e.g., Lester et al 2008) or, from a reverse-causality perspective, that politicians prefer to work for well-established and high-performing companies for reputational reasons. Recent work has started to address this issue.…”
Section: Public Versus Private Interests: Empirical Evidencementioning
confidence: 99%
“…It might simply be that firms benefit from moonlighting politicians via the introduction of important additional human and social capital (e.g., Lester et al 2008) or, from a reverse-causality perspective, that politicians prefer to work for well-established and high-performing companies for reputational reasons. Recent work has started to address this issue.…”
Section: Public Versus Private Interests: Empirical Evidencementioning
confidence: 99%
“…However, the effects of political connections on firm behavior and outcomes are not clear (Sun et al 2012). Many studies focus on the benefits from such linkages and indicate that political connections have a "buffering" effect; that is, they provide a buffer for the organization from competitive and regulatory forces via access to information, influence, and legitimacy (Hillman 2005, Hillman et al 1999, Lester et al 2008, Peng and Luo 2000. Research has shown that firms can employ their political capital to shield themselves from unwanted political interference, unfavorable regulations, and/or various forms of government rent expropriation (Mellahi et al 2016).…”
mentioning
confidence: 99%
“…С другой стороны, в случае, когда директора в течение дли-тельного периода работают в совете одной компании, их взгляд на деятельность и по-ложение дел в фирме становится не столь объективным. Работая в одной организа-ции, члены СД не всегда обладают знани-ями о новых открывающихся возможностях внешней среды, а функция мониторинга за деятельностью менеджмента выполняется уже не столь эффективно [Lester et al, 2008]. В то же время, в другой своей ра-боте [Hillman, Nicholson, Shropshire, 2008] авторы выдвигают и обосновывают предпо-ложение о том, что длительный срок на-хождения директора в должности влияет на силу его идентификации внутри компании и совета директоров и положительно вза-имосвязан с выполнением функций мони-торинга и обеспечения ресурсами.…”
Section: человеческий капитал совета директоровunclassified